[PP.38.01] THE RELATIONSHIP BETWEEN REGULAR PHYSICAL EXERCISE AND NOCTURNAL BLOOD PRESSURE IN KOREAN AMBULATORY BLOOD PRESSURE MONITORING (KORABP) STUDY. (September 2016) - Kim, B.; Shin, J.; Lim, Y.; Kim, S.
Abstract : Objective: There have been many reports showing that regular physical exercise can reduce the blood pressure (BP). Thus physical activity is one of the important component of lifestyle modification of hypertension. It is known that nocturnal BP is an independent factor for the cardiovascular event but there are few studies for the relationship between physical exercise and nocturnal BP. Design and method: Among 4145 subjects whose data for both clinical data and ambulatory blood pressure monitoring (ABPM) data file from the 5308 Korean ABPM (KorABP) study subjects, 3689 subjects were analyzed. The exclusion criteria was age less than 20 years (n = 84), missing data for the questionnaire for physical exercise (n = 372). Physical exercise was defined as regular structured exercise which intensity was heavier than the fast walking for 30 minutes. The count was recorded as the number per week. Results: Age was 55.5 ± 14.1 years and female was 45.9 %. Prevalence of hypertension, antihypertensive medication (AHM), diabetes and cardiovascular diseases were 58.9%, 32.5%, 13.0%, and 21.1%, respectively. Daytime and nighttime systolic BP was 138.5 ± 17.2 mmHg and 126.3 ± 18.8 mmHg. When adjusted for age, sex, BMI, and AHM, exercise frequency was independently decreased daytime systolic BP (beta = -0.52 mmHg per exercise, p = 0.02). For the nighttime systolic BP further adjusted by daytime systolic BP and sleep quality, exercise frequency was an independent factor (beta = -0.26 mmHg per exercise, p = 0.002). The statistical significances were observed even for only for 1 times per week. When further adjusted by smoking, exercise frequency was independent for nocturnal dipping (beta = 0.18% per exercise, p = 0.015) Figure. No caption available. Conclusions: Regular physical exercise is independently associated with lower nocturnal BP also lower daytime BP and with increased nocturnal dipping, which was independent of AHM and sleep quality.